Development of Si Yokca Application-Based Services at Grhatama Pustaka Yogyakarta - Susilawati, Ida; Laugu, Nurdin (Syarif Hidayatullah State Islamic University of Jakarta, 2023)
The development of online application-based library services has experienced significant growth in recent years. The evolving digital era has opened up opportunities for libraries to utilize modern technology to improve user services. The use of online applications is a significant aspect of this development, allowing users to access the library catalog, borrow and return books online, and access electronic resources quickly and efficiently. With this ease of access, users have a more significant opportunity to explore the library collection and utilize the available resources. This research discusses the development of online application-based services at Grhatama Pustaka Yogyakarta. The method used is qualitative, with observation and interview data collection techniques. This research uses the concept of the nature of services related to all forms of information needed by library users and the means of searching for information available in the library. The results showed that the management of the Si Yokca application as a whole has experienced rapid development, which provides efficient access to users. The application provides various features and services that can assist users in retrieving information independently. The latest innovation from the application is the availability of the Delivery Order service, which allows users to borrow collections without having to come directly to the library. This research contributes to the understanding of the development of online application-based library services, the efficiency of user access, and innovations such as Delivery Order services for borrowing collections